The first American Music Study group in Ghana: an unofficial report - Pantaleoni, Hewitt (International Library of African Music, 1968)
The University of California at Berkeley offered a four-week extension course entitled “Africa: its music and related arts”. One week was spent on the Berkeley campus and three weeks in Africa. Enrollment was allowed for just the first week, as well as for the full course. Well over one hundred attended the Berkeley sessions, and thirty-two went on to Africa.
Keywords: African Music; Ghana